Optimised accelerated solvent extraction of hexahydro‐1, 3, 5‐trinitro‐1, 3, 5 triazine (RDX) from polymer bonded explosives - Temple, Tracey; Goodwin, Catherine; Ladyman, Melissa K.; Mai, Nathalie; Coulon, Frederic (Wiley, 2018)
An Accelerated Solvent Extraction (ASE) method was developed and optimised to extract hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine (RDX) from a polyurethane matrix. The ASE method development was benchmarked against Soxhlet extraction with a view to improving extraction efficiency in terms of time and solvent volume. Key parameters for the ASE method development involved selecting the most appropriate solvent, optimising static time, ensuring a safe oven temperature for explosives, determination of a sufficient number of rinse cycles and effective sample preparation. To achieve optimal extraction, cutting the PBX samples to maximise solvent exposure was essential. The use of acetone with a static time of 10 minutes at 100 °C with three rinse cycles achieved 97 %±10 % extraction of RDX from PBX in 40 minutes using 72 mL solvent. Extraction time was reduced from 48 hours and solvent use by half compared to the standard Soxhlet extraction. To validate the developed ASE method, two other PBX samples containing different quantities of explosive were also fully extracted using the same parameters. Overall, ASE efficiency was comparable to Soxhlet, which places the ASE as a good alternative and shows potential for implementation as a standard method for other polymer based explosives.
Keywords: RDX; ASE method; pressurised solvent extraction; Soxhlet extraction; PBX